Exploring Teachers’ Perception and Assessment Practices in Differentiated English Instruction - Putu Diah Marcelina Putri; Ni Luh Putu Eka Sulistia Dewi; A .A. Gede Yudha Paramartha (STKIP AGAMA HINDU SINGARAJA, 2025)
This study investigated English teachers’ perceptions of assessment in differentiated instruction (DI) and the challenges encountered in its implementation at SMP Negeri 1 Singaraja. Employing a qualitative case study approach, data were collected through questionnaires and semi-structured interviews with four English teachers. The findings reveal that teachers perceive assessment within DI as a vital tool for identifying students’ readiness, supporting instructional differentiation, enhancing motivation, and aligning learning activities with clear objectives. Teachers also emphasize the importance of using varied assessment methods to accommodate diverse learning styles and profiles. However, several challenges emerged, including large class sizes, time constraints, creativity demanded, student disengagement, and difficulties in maintaining fairness. These findings highlighted the gap between theoretical ideals and practical realities, underscoring the need for targeted professional development and systemic support. The study contributes to the growing body of research on differentiated instruction in the Indonesia educational context and offers insights into how assessment can be better integrated to support inclusive and equitable learning.